Pengaruh Store Atmosphere Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Owners Store Tanjung Tabalong - Nadi Fikri Rijali; Emy Rahmawati (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
This study was conducted to determine and examine the effect of Store Atmosphere and Service Quality on Customer Satisfaction at Owners Store Tanjung Tabalong.The method in this study used a questionnaire as data collection with a sample of 85 respondents with the sampling technique used purposive sampling. Data processing in this study using the Statistical Product and Service Solutions (SPSS) program.The results showed that Store atmosphere did not have a significant effect on customer satisfaction at Owners Store Tanjung Tabalong, and service quality had a significant influence on customer satisfaction at Owners Store Tanjung Tabalong. Keywords: Fashion, Store Atmosphere, Quality Service, Customer Satisfaction